The Concept of Human Essence in Hegel and Marx - Noonan, Jeffrey R. (My University, 1993)
Postmodern thought has staked much of its claim to originality upon a critique of the concept of essence in previous philosophical systems. This critique is based upon the claim that essence has and must function as a reductionist and transcendent category. In so far as traditional metaphysics has applied this concept to humanity, it has inevitably posited the truth of humanity in a static and ahistorical manner. The following thesis has attempted to problamatize the postmodern reading through an examination of the works of Hegel and Marx.
Hegel's Phenomenology of Spirit is a revolutionary philosophical text in so far as it presents human history as a process in which the human community produces and transforms its essential nature. The human essence is transposed from an abstract realm superior to history into the very midst of historical being. Hegel's analysis discloses that the human essence is the capacity for selfcreation, or, in other words, positive freedom. History is understood to be the human struggle to make this essence a socio-political reality. In the course of this struggle the essence is itself transformed in the various attempts to make it a living reality.
If the human essence is the unique capacity to create oneself, then the dynamism implied takes on a critical function. It provides an evaluative criterion to measure given societies as regards freedom which is immanent to these societies and does not have to be imported from any abstract moral or religious system. The flushing out of the critical potential of this concept, left unrealized by Hegel, is the primary philosophical contribution of Marx. through a further concretization of the concept, Marx is able to establish a contrast between what a given society concretely offers its citizens, and the potential it creates but cannot, for systemic reasons, realize. Because the essence is rooted in the practical conditions of existence, it is a non-arbitrary, verifiable tool of critique. Furthermore, because it reveals how the self-creative character of humanity is artificially limited, it is also non-dogrnatic. No definite way of living is prescribed, the sale imperitive is to establish a society in which the material preconditions for the free self-realization of all individuals are met.
Keywords: Philosophy; Philosophy